Effect of nickel addition on enhancing nano-structuring and suppressing TRIP effect in Fe40Mn40Co10Cr10 high entropy alloy during high-pressure torsion - Chandan, Avanish Kumar; Kishore, Kaushal; Hung, Pham Tran; Ghosh, Mainak; Chowdhury, Sandip Ghosh; Kawasaki, Megumi; Gubicza, Jenő (International journal of plasticity, 2022)
•Ni addition to Fe40Mn40Co10Cr10 HEA altered the HPT-induced plasticity mechanisms.•Ni added alloy showed greater tendency for nano-structuring.•Ni addition led to suppression of TRIP mechanism.•A four-fold increase in dislocation density was obtained in the Ni added alloy.•A greater peak hardness was achieved in the Ni added alloy. The present work unravels the effect of nickel (Ni) addition on the deformation mechanism and hardness evolution in a Fe40Mn40Co10Cr10 high entropy alloy (HEA) during high-pressure torsion (HPT) processing. For this purpose, two variants of the high entropy Cantor alloy, with compositions (atomic%) Fe40Mn40Co10Cr10 (Ni0 alloy) and Fe35Mn35Co10Cr10Ni10 (Ni10 alloy) were selected. The study revealed a transition in the predominant plasticity mechanism with addition of Ni from TRIP in Ni0 to dislocation slip in Ni10 alloy. Such transition of plasticity mechanism was the direct consequence of an increase in the free energy of phase transformation, ΔGγ→ε towards a more positive value with Ni addition. Interestingly, the Ni10 alloy showed a greater extent of nano-structuring than the Ni0 alloy with nearly three-fold refined grain sizes, that is, lesser than 30 nm in Ni10 alloy and ∼90 nm in Ni0 alloy. Furthermore, a 3–4 times higher dislocation density was observed in the FCC phase of the Ni10 alloy compared to that in the transformed HCP phase in the Ni0 alloy for any given HPT processing conditions. These differences in mechanism(s) of deformation and the extent of nano-structuring manifested as a greater ability of Ni added Ni10 alloy to harden itself during HPT. The present study suggests that a large fraction of hard HCP phase originating from TRIP effect in the Ni0 alloy has a lower hardening ability than the high dislocation density and nano-structuring in the Ni10 alloy. [Display omitted] .